PREDIKSI FINANCIAL DISTRESS DENGAN MODEL ALTMAN DAN ZMIJEWSKI - Regita Puji Cahyani; Dewa Gede Wirama (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the prediction of financial distress in all non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period using the Altman Z-Score Model and the Zmijewski Model, as well as to compare the predictive accuracy of the two models. Financial distress is a condition in which a company experiences financial difficulties that may lead to bankruptcy. This research employs a quantitative approach with a descriptive method. A total sample of 250 companies was determined using stratified random sampling and analyzed with the non-parametric Mann-Whitney test, along with prediction accuracy testing using the bootstrapping method. The results indicate a significant difference between the Altman and Zmijewski models in predicting financial distress. Furthermore, the Zmijewski model demonstrates a higher predictive accuracy of 95.1% compared to 89.6% for the Altman model. These findings are expected to provide both theoretical and practical contributions, particularly in decision-making processes for company management, investors, and creditors.